Anatomical characterization and physical properties of coppiced wood of two Quercus species from the Popocatepetl volcano - Ortega-Gutiérrez, José Octavio; Alvarado-Segura, Arturo A.; Machuca-Velazco, Roberto; Borja-de-la-Rosa, Amparo (Instituto de Ecología, A.C., 2023)
Mexico has at least 179 species of the genus Quercus, which include some of the most important species for coppice forestry. Coppice forestry, the differentiated treatments and the use of wood based on its technological characteristics, could contribute to optimize the use of the goods and services provided by Quercus species. In this work we evaluated the anatomical characteristics and some physical properties of coppiced wood from Quercus laurina and Quercus obtusata, species used to obtain charcoal and firewood in the communities surrounding the Popocatepetl volcano in Puebla, Mexico. The anatomical characteristics reported in this study coincide with previous descriptions of the wood from monostem trees, except for the presence of helical thickenings in fibers and annular porosity observed in Quercus obtusata. Regarding physical properties, values lower than those previously reported by other authors were recorded. It is suggested to carry out silvicultural trials of coppicing method on Quercus species and to evaluate the technological characteristics of the resulting wood.